2019
DOI: 10.1007/s12599-018-00573-0
|View full text |Cite
|
Sign up to set email alerts
|

Framing Microgrid Design from a Business and Information Systems Engineering Perspective

Abstract: Microgrids are decentralized distribution networks that integrate distributed energy resources and balance energy generation and loads locally. The introduction of microgrids can help overcome the challenges of global energy systems. Despite this potential, the information systems domain has seen limited research on microgrids. This paper synthesizes research on elements of microgrids for electric energy. Interviewed experts maintain that technological microgrid solutions have been solidly developed; neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 78 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…This sees different challenges and opportunities emerge that are discussed below. [11] observed that while the technological foundations for establishing and operating MGs are sound, the lack of economics and business considerations is stalling their progress. According to ([12] p. 2) the MG business model is defined by "the plan of the organization for successful operation of the business, determining revenue stream, target customer, product and financial model."…”
Section: Emerging Challenges and Opportunitiesmentioning
confidence: 99%
“…This sees different challenges and opportunities emerge that are discussed below. [11] observed that while the technological foundations for establishing and operating MGs are sound, the lack of economics and business considerations is stalling their progress. According to ([12] p. 2) the MG business model is defined by "the plan of the organization for successful operation of the business, determining revenue stream, target customer, product and financial model."…”
Section: Emerging Challenges and Opportunitiesmentioning
confidence: 99%
“…In [5] it is proposed to consider Microgrid not only as energy technologies for the production, storage, distribution and consumption of energy, but also with a focus on the information component. Microgrid as a structure should be considered in addition to political, economic, social, technological, legal and environmental factors.…”
Section: Fig 11 a Typical Multi-microgrid Schemementioning
confidence: 99%
“…Compared to traditional power grids, the developed information and communication infrastructure provides arrays of data that can be collected and processed in real time. It is subject to the requirements of reliability, safety, scalability and ease of management [7].…”
Section: Fig 21 Microgrid Implementation Processmentioning
confidence: 99%
“…This section presents issues that can be relevant in the context of the Brazilian regulation based on this study. Microgrids are not currently defined as entities in the existing regulation in the international electricity sector, neither in the Brazilian context [15].…”
Section: Challenges For the Insertion And Aggregation Of Microgridmentioning
confidence: 99%